(untitled) - Teubes, Megan

Sustainable management of breech flystrike in sheep by manipulating tail length: the effect of tail docking on lamb welfare as well as the genetics of ovine tail length (Stellenbosch : Stellenbosch University, 2024)
Thesis (MScAgric)--Stellenbosch University, 2024.